Negotiating Authenticity in Instagram Influencer Endorsements: Audience Trust, Purchase Intention, and Digital Promotion - Desmanur Tsalatsa; Harry Fajar Maulana; Hastuti Hastuti (Jogjakarta Communication Conference (JCC), 2026)
The growth influence of marketing on social media has transformed the way brands communicate with audiences, particularly on visually driven platforms such as Instagram. Within this environment, authenticity has emerged as a critical factor influencing audience engagement and the effectiveness of endorsement messages. This study aims to examine how authenticity is constructed in influencer endorsement practices and how audiences interpret and respond to such authenticity in the context of Instagram. This research employs a qualitative approach using in-depth interviews and digital observation to explore the perspectives of influencers, audience members, and small business owners who have collaborated with influencers. Data was analyzed using thematic analysis to identify patterns of meaning related to authenticity, trust, consumer response, and business impact in influencer endorsement communication.  The findings reveal that audiences interpret authenticity primarily through honest communication, natural storytelling, and the perceived sincerity of influencers when presenting products. Authenticity plays a central role in building audience trust, which subsequently shapes how audiences evaluate endorsement messages and influences their intention to try or purchase promoted products. The results also indicate that influencer endorsements can generate significant promotional benefits for small businesses by increasing visibility, online engagement, and consumer interest. These findings suggest that authenticity functions as a relational communication process that mediates the relationship between influencers, audiences, and commercial partners. Understanding authenticity as a negotiated and interactive construct provides important insights into digital marketing strategies and contributes to the broader study of influencer communication in the digital economy.